Dental Health in Smokers with and without COPD - Bergström, Jan (Public Library of Science, 2013)
The association between chronic obstructive pulmonary disease (COPD) and periodontal disease is sparsely studied. The aim was to describe the co-variation of periodontitis and lung function impairment in smokers. The hypothesis was that the destructive processes in the mouth and the lungs are interdependent due to a general individual susceptibility to detrimental effects of tobacco smoke. Smokers with COPD (n = 28) stage II and III according to GOLD guidelines and smokers without COPD (n = 29) and healthy non-smokers (n = 23) participated in the study. The groups of smokers were matched for cumulative exposure to tobacco smoke. Radiographic, general and dental clinical examination, lung function measurements and quality of life (SF-36) assessment were conducted. The relationship between respiratory and dental outcomes was analyzed. Dental health, assessed by plaque, gingival bleeding, periodontal pocket depth and loss of teeth was impaired in the smokers compared with non-smokers with no major differences between smokers with and without COPD. There was, however, a weak correlation between periodontitis and emphysema/impaired diffusion capacity. Impaired quality of life was associated with smoking and impaired lung function but not influenced by dental status. In conclusion periodontitis was strongly associated with smoking, weakly associated with lung tissue destruction and very weakly or even not at all associated with chronic airflow limitation. The results indicate that, although there was a co-variation between periodontitis and pathologic lung processes in smokers, the risk of developing COPD, as defined by spirometric outcomes, is not associated with the risk of impaired dental health in smokers.